2019
DOI: 10.3390/catal9070620
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of a Novel ESTBAS Esterase from Bacillus altitudinis onto an Epoxy Resin: Characterization and Regioselective Synthesis of Chloramphenicol Palmitate

Abstract: Novel gene estBAS from Bacillus altitudinis, encoding a 216-amino acid esterase (EstBAS) with a signal peptide (SP), was expressed in Escherichia coli. EstBASΔSP showed the highest activity toward p-nitrophenyl hexanoate at 50 °C and pH 8.0 and had a half-life (T1/2) of 6 h at 50 °C. EstBASΔSP was immobilized onto a novel epoxy resin (Lx-105s) with a high loading of 96 mg/g. Fourier transform infrared (FTIR) spectroscopy showed that EstBASΔSP was successfully immobilized onto Lx-105s. In addition, immobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…53 Besides, immobilized esterase Lx-Est BAS ΔSP activity was reduced by 3% in the presence of Zn 2+ whereas Mg 2+ increased its activity by 8%. 45 The surfactant analysis result showed that SDS completely inhibited the immobilized esterase activity whereas Triton X-100 strongly decreased by 42% (Fig. 4).…”
Section: Effect Of Chemicalsmentioning
confidence: 94%
See 4 more Smart Citations
“…53 Besides, immobilized esterase Lx-Est BAS ΔSP activity was reduced by 3% in the presence of Zn 2+ whereas Mg 2+ increased its activity by 8%. 45 The surfactant analysis result showed that SDS completely inhibited the immobilized esterase activity whereas Triton X-100 strongly decreased by 42% (Fig. 4).…”
Section: Effect Of Chemicalsmentioning
confidence: 94%
“…50 An immobilized esterase Lx-Est BAS ΔSP also showed higher stability than free esterase Est BAS ΔSP and retained about 80% of residual activity at 60°C after 1 h of incubation. 45 Furthermore, two immobilized Mucor miehei esterase on core-shell magnetic beads via adsorption and covalent binding showed 80% and 90% of residual activity at 60°C, respectively. 27 There have been reported some studies on the thermal stability of free and immobilized esterase from various sources, showing much lower thermal stability, compared to the present study.…”
Section: Thermal Stabilitymentioning
confidence: 96%
See 3 more Smart Citations